Design of trainer kit as a fault-finding based on electricity and electronics learning media - Muhammad Anwar; Mochamad Bruri Triyono; Ta'ali Ta'ali; Hendra Hidayat; Veva Nellone Syahputeri (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
According to the field of expertise, efforts to strengthen the competence of graduates continue to be pursued, especially through optimizing the learning process. Among these efforts is to use learning media that strengthen the competence of the field of study and about thinking skills. This study aims to produce a trainer kit as a medium for learning basic electricity and electronics based on fault-finding in Basic Electrical and Electronics subjects. The method used is the Richey and Klein Design and Development (D&D) method which consists of three stages, including planning (design), production, and evaluation. Experts carried out the assessment of the feasibility of the trainer kit with an instrument in the form of a questionnaire. The results of this study indicate that the trainer kit has a good performance.According to the field of expertise, efforts to strengthen the competence of graduates continue to be pursued, especially through optimizing the learning process. Among these efforts is to use learning media that strengthen the competence of the field of study and about thinking skills. This study aims to produce a trainer kit as a medium for learning basic electricity and electronics based on fault-finding in Basic Electrical and Electronics subjects. The method used is the Richey and Klein Design and Development (D&D) method which consists of three stages, including planning (design), production, and evaluation. Experts carried out the assessment of the feasibility of the trainer kit with an instrument in the form of a questionnaire. The results of this study indicate that the trainer kit has a good performance.